Evaluation of the melatonin and oxidative stress markers level in serum of fertile and infertile women - Sara Soleimani Rad; Shamsi Abbasalizadeh; Amir Ghorbani Haghjo; Mehzad Sadagheyani; Azadeh Montaseri; Jafar Soleimani Rad (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Infertility is defined as the inability to achieve the pregnancy within a year of unprotected intercourse. Infertility is a complex issue and different factors such as stress oxidative can be involved in this problem. So, any attempt to neutralize oxidative stress would be helpful in the treatment of infertility. Melatonin is a known scavenger of free radicals. Objective: The aim of our study was to evaluate the level of melatonin and its correlation with oxidative biomarkers in fertile and infertile women. Materials and Methods: The participants including fertile and infertile women were divided into two groups of 30 people. Blood sampling was performed and sera were collected. The level of Malondialdehyde (MDA), total antioxidant capacity (TAC) and melatonin were detected. Data were analyzed using T-test and their correlation was assessed using Spearman test. Results: Serum melatonin from fertile women was higher than infertile women but the difference was not significant (p= 0.46). MDA level in fertile women was significantly lower than infertile women (p<0.001) and the level of TAC in fertile women was significantly higher than infertile women (p<0.001). Spearman test revealed a significant and direct correlation between melatonin and TAC in fertile and infertile women and a significant but reverse correlation between melatonin and MDA in infertile and fertile women. Conclusion: Differences in the level of oxidative stress biomarkers in fertile and infertile individuals have been reported. This study revealed a significant correlation between melatonin and oxidative stress biomarkers, concluding that melatonin level could be involved in infertility.